Promoting STI testing among senior vocational students in Rotterdam, the Netherlands: effects of a cluster randomized study - Wolfers, Mireille (BioMed Central, 2011)
BACKGROUND: Adolescents are a risk group for acquiring sexually transmitted infections (STIs). In the Netherlands, senior vocational school students are particular at risk. However, STI test rates among adolescents are low and interventions that promote testing are scarce. To enhance voluntary STI testing, an intervention was designed and evaluated in senior vocational schools. The intervention combined classroom health education with sexual health services at the school site. The purpose of this study was to assess the combined and single effects on STI testing of health education and school-based sexual health services. METHODS: In a cluster-randomized study the intervention was evaluated in 24 schools, using three experimental conditions: 1) health education, 2) sexual health services; 3) both components; and a control group. STI testing was assessed by self reported behavior and registrations at regional sexual health services. Follow-up measurements were performed at 1, 3, and 6-9 months. Of 1302 students present at baseline, 739 (57%) completed at least 1 follow-up measurement, of these students 472 (64%) were sexually experienced, and considered to be susceptible for the intervention. Multi-level analyses were conducted. To perform analyses according to the principle of intention-to-treat, missing observations at follow-up on the outcome measure were imputed with multiple imputation techniques. Results were compared with the complete cases analysis. RESULTS: Sexually experienced students that received the combined intervention of health education and sexual health services reported more STI testing (29%) than students in the control group (4%) (OR = 4.3, p < 0.05). Test rates in the group that received education or sexual health services only were 5.7% and 19.9%, not reaching statistical significance in multilevel analyses. Female students were more often tested then male students: 21.5% versus 5.4%. The STI-prevalence in the study group was low with 1.4%. CONCLUSIONS: Despite a low dose of intervention that was received by the students and a high attrition, we were able to show an intervention effect among sexually experienced students on STI testing. This study confirmed our hypothesis that offering health education to vocational students in combination with sexual health services at school sites is more effective in enhancing STI testing than offering services or education only.